2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4650183
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency dosimetry in subjects implanted with metallic straight wires: A numerical study

Abstract: A numerical study to investigate the effects of the exposure to electromagnetic fields (EMF) at 900 and 1800 MHz on biological tissues implanted with thin metallic structures has been carried out, using the finite difference time domain (FDTD) solution technique. The results of the model show that the presence of a metallic wire yields to a significant increase in the local specific energy absorption rate (SAR). The present standards and/or guidelines on safe exposures of humans to EMF does not cover persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Dr. Irnich commented that “The deciding distance for considering heat induction is not the absolute length but the distance between lead tip and the metallic case in attached leads or between lead tip and the insulated lead connector of the abandoned lead respectively.” We respectfully disagree with this theory based on our findings, the previous findings of others 1–5 that highlight the effect of lead length on pacemaker lead tip heating, and the lack of peer‐reviewed published evidence favoring this theory.…”
contrasting
confidence: 87%
“…Dr. Irnich commented that “The deciding distance for considering heat induction is not the absolute length but the distance between lead tip and the metallic case in attached leads or between lead tip and the insulated lead connector of the abandoned lead respectively.” We respectfully disagree with this theory based on our findings, the previous findings of others 1–5 that highlight the effect of lead length on pacemaker lead tip heating, and the lack of peer‐reviewed published evidence favoring this theory.…”
contrasting
confidence: 87%
“…Finite difference time domain computer simulations were used to examine the effect of a local conductivity change on the local electric field with and without a wire implant. A simple insulated wire is often used in computer simulation as a representation of pacemaker leads (4, 6, 18–20). Our electromagnetic modeling did not include a realistic pacemaker lead owing to the formidable complexity of including one in a finite difference time domain electromagnetic field simulation.…”
Section: Discussionmentioning
confidence: 99%
“…[41] It was reported that 900 and 1800 MHz plane waves can result in temperature rises around the implant with less than 0.25 C and 0.10 C, respectively. [42] On the other hand, compared to stainless steel, titanium alloy, which is frequently preferred in medical implants, have low magnetic permeability and electric conductivity. Therefore, lesser increases in temperature have been reported secondary to RF applications around implants with titanium alloy.…”
Section: Histopathological Analysismentioning
confidence: 99%